Explor Dig Dis 2022
DOI: 10.37349/edd.2022.00012
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia signaling and cholesterol/steroidogenic acute regulatory protein 1 axis: interplay and role in alcohol and non-alcohol-related liver diseases

Abstract: Metabolic zonation in the liver carries out the maintenance of organ and body homeostasis. Hypoxia is an inherent physiological feature of the liver and contributes to the zonal properties of the hepatic parenchyma. As a master regulator of hypoxia, the transcription factor hypoxia-inducing factor (HIF) is stabilized primarily by oxygen availability, and it is thought to contribute to steatohepatitis due to alcohol-related (ASH) and non-alcohol-related liver disease (NASH). Cholesterol has emerged as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 127 publications
0
1
0
Order By: Relevance
“…The mechanisms underlying the impact of alcohol metabolism on ALD are multifactorial and involve alterations in methionine metabolism, ER stress, disruption of lipid metabolism, genetic and environmental factors, and mitochondrial dysfunction with changes in mitochondrial dynamics, respiration, changes in membrane composition, mitochondrial DNA oxidation and ROS production [ 110 ]. Recent findings indicated that ALDH2, which plays a critical role in the detoxification of acetaldehyde produced during ethanol metabolism, regulates cholesterol synthesis [ 111 ].…”
Section: Mitochondrial Cholesterol Accumulation In Diseasementioning
confidence: 99%
“…The mechanisms underlying the impact of alcohol metabolism on ALD are multifactorial and involve alterations in methionine metabolism, ER stress, disruption of lipid metabolism, genetic and environmental factors, and mitochondrial dysfunction with changes in mitochondrial dynamics, respiration, changes in membrane composition, mitochondrial DNA oxidation and ROS production [ 110 ]. Recent findings indicated that ALDH2, which plays a critical role in the detoxification of acetaldehyde produced during ethanol metabolism, regulates cholesterol synthesis [ 111 ].…”
Section: Mitochondrial Cholesterol Accumulation In Diseasementioning
confidence: 99%